2015
DOI: 10.1111/gcb.12882
|View full text |Cite
|
Sign up to set email alerts
|

Too much of a good thing: sea ice extent may have forced emperor penguins into refugia during the last glacial maximum

Abstract: The relationship between population structure and demographic history is critical to understanding microevolution and for predicting the resilience of species to environmental change. Using mitochondrial DNA from extant colonies and radiocarbon-dated subfossils, we present the first microevolutionary analysis of emperor penguins (Aptenodytes forsteri) and show their population trends throughout the last glacial maximum (LGM, 19.5-16 kya) and during the subsequent period of warming and sea ice retreat. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
63
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(73 citation statements)
references
References 86 publications
8
63
0
2
Order By: Relevance
“…3). Given their adaptation to the cold and apparent obligate requirement to use sea ice as a breeding platform, it has been hypothesised that emperor penguins may have prospered during the LGM [56], although our genetic data indicate that past emperor penguin populations were not favoured during periods of glaciation [40]. Indeed, the N ef for emperor penguins only increased to present day values following the end of the LGM.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…3). Given their adaptation to the cold and apparent obligate requirement to use sea ice as a breeding platform, it has been hypothesised that emperor penguins may have prospered during the LGM [56], although our genetic data indicate that past emperor penguin populations were not favoured during periods of glaciation [40]. Indeed, the N ef for emperor penguins only increased to present day values following the end of the LGM.…”
Section: Discussionmentioning
confidence: 79%
“…A continent-wide genetic study of emperor penguin population structure also found that the penguins were panmictic across ca. 8,000 km of coastline [40]. Together, these studies strongly refute total philopatry among emperor penguins, and this must be taken into account in population forecasting studies for emperor penguins, which typically consider breeding colonies as isolated units [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations